The Provisions of War : Expanding the Boundaries of Food and Conflict, 1840-1990 - Nordstrom, Justin (Book collections on Project MUSE., 2021)
"This collection of essays examines how food and its absence have been used both as a destructive weapon and a unifying force in establishing governmental control and cultural cohesion during times of conflict"--